Role of Product Quality and Store Atmosphere on Purchase Decision of Clothing Product Vintage Vibes - Siti Aisyah; Chairul Anwar; Nugroho Djati Satmoko; Sutrisno; Uli Wildan Nuryanto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The objectives of this study is to examine role of product quality and store atmosphere on purchase decision of clothing product of Vintage Vibes. This research uses quantitative research. This study aims to analyze the influence of product quality and store atmosphere on purchasing decisions at Vintage Vibes. In this study, there are two kinds of variables, namely the independent variable and the dependent variable. The independent variables in this study are product quality and the atmosphere in the store, while the dependent variable is purchasing decisions. The unit of analysis in this study is "vintage vibes," with the criteria being namely those who have purchased fashion products at Vintage Vibes. The result of this study show that product quality has a positive effect on purchase decisions. Store atmosphere has an influence on purchase decision. Product quality and store atmosphere have a joint effect on purchase decision.